EFEKTIVITAS FRAKSI AKTIF EKSTRAK ETANOL LABU SIAM (Sechium edule (Jack) Sw) SEBAGAI ANTIHIPERTENSI PADA TIKUS HIPERTENSI YANG DIINDUKSI MONOSODIUM GLUTAMAT - Yance Anas; Ika Nilam Cahyani; Ulum Firnanda Sukma (Jurnal Ilmu Farmasi dan Farmasi Klinik, 2021)
ABSTRACT Previous studies accomplished that the chayote ethanol extract (Sechium edule (Jack) Sw) had an antihypertensive effect. To get and identify the active compound, we fractionated the extract and evaluated its antihypertensive activity. This study aims to investigate the antihypertensive effect of the n-hexane fraction (HF-CEE) and ethyl acetate fraction of chayote ethanol extract (EAF-CEE) in monosodium glutamate (MSG)-induced hypertensive rats. We made the chayote extract using the maceration method by soaking the chayote simplicia in ethanol 70%. HF-CEE and EAF-CEE were obtained by stratified fractionation using n-hexane and ethyl acetate. An antihypertensive effect of the fraction measured on MSG-induced hypertension male Wistar rats after MSG 100 mg/kg BW/day (p.o) treatment for 14 days. The study concluded that HF-CEE and EAF-CEE had an antihypertensive effect in MSG-induced hypertensive rats. The EAF-CEE antihypertensive effect is higher than HF-CEE. Therefore, the FEAF-CEE active compounds need to be isolated, identified, developed, and their potential as an antihypertensive candidate. Keywords: Antihypertensive, chayote, ethyl-acetate fraction, Sechium edule, monosodium glutamate